2014
DOI: 10.1162/jocn_a_00493
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Parieto-premotor Network for Mental Image Transformation Revealed by Simultaneous EEG and fMRI Measurement

Abstract: Previous studies have suggested that the posterior parietal cortices and premotor areas are involved in mental image transformation. However, it remains unknown whether these regions really cooperate to realize mental image transformation. In this study, simultaneous EEG and fMRI were performed to clarify the spatio-temporal properties of neural networks engaged in mental image transformation. We adopted a modified version of the mental clock task used by Sack et al. [Sack, A. T., Camprodon, J. A., Pascual-Leo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
4
19
0
Order By: Relevance
“…This latter possibly encodes the motor aspect of mental rotation. This is in line with previous studies which used similar experimental protocols and observed the activation of SMA28 and PMC33. During mental rotation of hands we also found the activation of BG.…”
Section: Discussionsupporting
confidence: 93%
“…This latter possibly encodes the motor aspect of mental rotation. This is in line with previous studies which used similar experimental protocols and observed the activation of SMA28 and PMC33. During mental rotation of hands we also found the activation of BG.…”
Section: Discussionsupporting
confidence: 93%
“…The results related to increased beta suppression enabled by neurofeedback above the left parietal cortex at the early stage and above the right parietal cortex at the late stage of mental rotation are consistent with the findings reported by Sasaoka et al (2014). Using simultaneous EEG and fMRI measurements, these researchers established that the process of mental image transformation is accompanied by beta-band desynchronisation observed bilaterally in the parietal cortices.…”
Section: Discussionsupporting
confidence: 92%
“…Time–frequency characterisation of brain activity during performance of the Shepard–Metzler task shows a dominant role of beta-band suppression, although this effect was usually linked to tasks engaging motor imagery (Engel and Fries 2010; Nam et al 2011; Wang et al 2016). Simultaneously conducted fMRI and EEG measurements showed a significant relation between beta ERD and the process of mental transformation of objects (Sasaoka et al 2014). Sasaoka and colleagues established that increased activation in bilateral parietal cortex and the left premotor cortex is accompanied with greater beta-band suppression during the mental transformation of objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is particularly important as there are often multiple sources of EEG, and distinguishing these sources can give important insight into the workings of the brain. For example, when recording motor related potentials, various cortical regions may be active simultaneously such as during visually guided movements [ 9 ] or while performing motor tasks requiring mental image transformations [ 10 ]. Accurately reconstructing this activity would allow for the study of how cortical regions are associated with various motor tasks.…”
Section: Introductionmentioning
confidence: 99%